She could try to reduce variable costs
Answer:
a = -2
Simplifying 5 + -2(4a + 1) + 3a = 13 Reorder the terms: 5 + -2(1 + 4a) + 3a = 13 5 + (1 * -2 + 4a * -2) + 3a = 13 5 + (-2 + -8a) + 3a = 13 Combine like terms: 5 + -2 = 3 3 + -8a + 3a = 13 Combine like terms: -8a + 3a = -5a 3 + -5a = 13 Solving 3 + -5a = 13 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -5a = 13 + -3 Combine like terms: 3 + -3 = 0 0 + -5a = 13 + -3 -5a = 13 + -3 Combine like terms: 13 + -3 = 10 -5a = 10 Divide each side by '-5'. a = -2
Answer:
13
Step-by-step explanation:
where n is the number of terms, a1 is the first term and an is the last term. The sum of the first n terms of an arithmetic sequence is called an arithmetic series . Example 1: Find the sum of the first 20 terms of the arithmetic series if a1=5 and a20=62 .An arithmetic sequence is a sequence where the difference between any two consecutive terms is a constant. ... As with any recursive formula, the initial term of the sequence must be given. An explicit formula for an arithmetic sequence with common difference d is given by an=a1+d(n−1) a n = a 1 + d ( n − 1 ) .
Answer:
The end behavior of f(x)=2/3x-2 is: as x->+ infinity, f(x)->+ infinity
as x->- infinity, f(x)->- infinity
Step-by-step explanation:
When you are asked about the end behavior of a function, look to see where the function is traveling on the graph. For instance, this graph is linear, so you should look to see if the slope is positive or negative. This linear function is positive, so as x is reaching positive infinity the f(x) would also be reaching positive infinity. As x is reaching negative infinity, f(x) would also be reaching negative infinity. The end behavior of a function describes the trend of the graph on the left and right side of the x- axis. (As x approaches negative infinity and as x approaches positive infinity).